Penerapan metode multisensori untuk meningkatkan kemampuan membaca pada siswa UPT SD Negeri 7 Gresik - Vina, Erviana; Endah, Noer Suci (Journal of Smart Education and Learning, 2025)
This study aims to improve students' reading ability by applying the multisensory method at UPT SD Negeri 7 Gresik. The multisensory method involves the senses of sight, hearing, movement, and touch during learning activities. The research subjects were four third-grade students with reading difficulties. Data were collected through observation, interviews, and documentation. The intervention was carried out six times using media such as letter puzzles, flour media, reading practice books, and cardboard boards. The results showed that the multisensory method helped improve students' reading ability, especially in recognising letters, combining syllables, and reading fluently. However, each student showed different levels of improvement depending on their initial ability and participation during the intervention. The multisensory approach made the learning process more concrete, interesting, and interactive for students.